KAJIAN USAHATANI BAWANG MERAH DENGAN PAKET TEKNOLOGI GOOD AGRICULTURE PRACTICES - Sortha Simatupang; Tumpal Sipahutar; Andriko Noto Sutanto (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2017)
Shallot Farming With Good Agriculture Practices Technology Package. The productivity of shallot at the farmer level in Dolok Silau Sub district, North Sumatera Province is still low that is 4-5.25 ton/ha. The area of shallot cultivation in North Sumatra continues to decrease, because the selling price of tubers often harms the farmers. This study aimed to determine the increase shallot productivity using Good Agriculture Practices (GAP) technology package. This assessment was an adaptive research in a farming system perspective with On Farm Client Oriented Adaptive Research (OFCOAR) approach. The assessment was carried out in three farmer groups in Sarang Padang Village, Dolok Silau Sub-district, North Sumatera Province, 2016. The total area of shallot farming was 1500 m2 . The GAP technology package increased production costs per hectare, but the cost of shallot production per kg became cheaper, equal to (58%) of the farmer's technological costs. B/C of GAP package was 3.21 or this value was higher than the farmer technology package by 0.60. The addition of one unit of production cost to the GAP technology package could increase revenue by 7.29 times the revenues earned by the usual technology applied by farmers. The analysis of competitive advantage showed that the minimum selling price of shallot was 6,844.9 IDR/kg. Farmers still gain a competitive advantage from shallot farming activities at production rate of 17 ton/ha with the application of GAP technology.shallot, package technology, GAP, production cost, revenue ABSTRAKProduktivitas bawang merah di tingkat petani di Kecamatan Dolok Silau, Provinsi Sumatera Utara masih rendah yaitu 4-5,25 ton/ha. Luas pertanaman bawang merah di Sumatera Utara terus berkurang, karena harga jual umbi yang sering merugikan petani. Kajian ini bertujuan untuk mengetahui peningkatan produktivitas bawang merah menggunakan paket teknologi Good Agriculture Practices (GAP). Pengkajian ini merupakan penelitian adaptif dalam perspektif sistem usahatani dengan pendekatan On Farm Client Oriented Adaptive Research (OFCOAR). Pengkajian dilaksanakan pada tiga kelompok tani di Desa Sarang Padang, Kecamatan Dolok Silau, Sumatera Utara, 2016. Luasan pertanaman bawang merah masing-masing kelompok tani 1500 m2 . Paket teknologi GAP tersebut meningkatkan biayaproduksi per hektar, tetapi biaya produksi bawang merah per kg menjadi lebih murah sebesar (58%) dari biaya teknologi petani. B/C paket GAP sebesar 3,21 atau nilai ini lebih tinggi dibandingkan paket teknologi petani sebesar 0,60. Penambahan satu satuan biaya produksi pada paket teknologi GAP dapat meningkatkan pendapatan sebesar 7,29 kali dari pendapatan yang diperoleh dengan teknologi yang biasa diterapkan petani. Analisis keuntungan kompetitif menunjukkan bahwa harga jual minimal bawang merah sebesar Rp6.844,9/kg. Petani masih memperoleh keuntungan kompetitif dari kegiatan usahatani bawang merah pada tingkat produksi 17 ton/ha dengan penerapan teknologi GAP.bawang merah, paket teknologi, GAP, biaya produksi, keuntungan